2020
DOI: 10.14569/ijacsa.2020.0110949
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Model for the Determination of Academic Performance in Private Higher Education Institutions

Abstract: The growth and development of predictive models in the current world has influenced considerable changes. Today, predictive modelling of academic performance has transformed more than a few institutions by improving their students' academic performance. This paper presents a computational predictive model using artificial neural networks to predict whether a student will pass or fail. The model is unique in the current literature as it is specifically designed to evaluate the effectiveness of the predictive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…To predict wither a student will pass or fail and to evaluate the effectiveness of the predictive strategies in the literature, the authors used (ANN) Artificial Neural Networks and five other algorithms. ANN performed better and the results showed that the students' performance6 is correlated with features like group assignments and if the student is bursary or not [28].…”
Section: Related Workmentioning
confidence: 99%
“…To predict wither a student will pass or fail and to evaluate the effectiveness of the predictive strategies in the literature, the authors used (ANN) Artificial Neural Networks and five other algorithms. ANN performed better and the results showed that the students' performance6 is correlated with features like group assignments and if the student is bursary or not [28].…”
Section: Related Workmentioning
confidence: 99%
“…Lottering et al (2020) applied predictive modelling techniques for 1,156 students to identify students at risk of dropping out of their registered qualification. Makombe and Lall (2020) worked on a computational predictive model using artificial neural networks to predict whether a student will pass or fail.…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that the values for these algorithms must be discrete values [27]. Among the classification algorithms is Kernel, which extends the regular logistic regression, used for binary classification, to deal with data that are not linearly separable [28].…”
Section: Introductionmentioning
confidence: 99%